Tato Arts Center in Badung, Bali - Maheswara, Made Bagus Angga; Prajnawrdhi, Tri Anggraini; Wiryawan, I Wayan (Journal of A Sustainable Global South; Vol 1 No 2 (2017): August 2017DO - 10.24843/jsgs.2017.v01.i02.p05, 2017)
The centre of arts was a place for activity that related to the arts itself, as a place to show the local art and culture, and provide us information about the artworks that made by the artist and show it to the visitors or consumers by displaying these artworks into art exhibition that expected to be able reach a wider market. This art centre published as a gallery that will accommodate tattoo artist to show their artwork as a paintings and tattoos on synthetic leather. The research of this study using qualitative method by spreading questionnaires, studying literature with local regulations including the application of the characteristics of traditional Balinese architecture that are harmoniously environmentally friendly, and field observation techniques on objects related to facilities found in art centers such as galleries, exhibitions and tattoo studios where the results of the research steps are the results of questionnaires with 70 respondents 98, 6% were in-terested in tattoo art and agreed to realize the planning of the Tattoo Art Center in Badung, The result of this literature study and observation were the architecture that used generally between Balinese architecture with modern architec-ture in the building that used neo vernacular concept. This building was applying the neo vernacular concept in the gallery section where the gallery facade applies the Tri Angga concept, such as the head, body and legs which were in traditional forms, using pyramid roofs which have mudras and participate in Ciledu and used local materials in the form of bricks and natural stones through application it produced concept of neo vernacular. Index Terms — neo vernacular, art center, tattoo, gallery, facade.